Model Persediaan Fuzzy dengan Kredit Perdagangan dan Kendala Kapasitas Gudang untuk Barang yang Mengalami Deteriorasi - Safitri, Addini; Subhan, Muhammad (Journal of Mathematics UNP, 2024)
Economic Order Quantity (EOQ) model is a model for inventory management decision-making. The basic EOQ model is not entirely realistic, as it neglects several factors that impact inventory management decisions, leading to suboptimal outcomes. This study aims to form and analyze the inventory model from the development of EOQ model. Market competition, seasonal changes, promotional reach, and unexpected events can cause uncertainty. Fuzzy set theory is used to overcome this uncertainty, namely demand rate and deterioration rate are represented by fuzzy numbers. Trade credit and limited capacity of the company’s warehouse are also considered, so the rented warehouse is used. The fuzzy model is deffuzified by graded mean integration representation method. Results include a model for optimal order quantity, the optimal time for rented warehouse inventory depletion, and the minimum total cost. Numerical simulation and sensitivity analysis demonstrate the model’s applicability and highlight the impact of parameter changes.